Does economic policy uncertainty in the U.S. influence stock markets in China and India? Time-frequency evidence. Issue 39 (20th August 2020) - Li, Rong; Li, Sufang; Yuan, Di; Yu, Keming
ABSTRACT: This paper uses continuous and discrete wavelet tools to evaluate the dynamic correlation and causality between the U.S. economic policy uncertainty (EPU) and stock markets in China and India from 1997 to 2018. The dynamic correlation in the time-frequency domain is obtained by continuous wavelet coherence, and the causality over time and frequencies is tested by the linear and non-linear Granger causality based on discrete wavelet transform. The results show that the interaction between EPU in the U.S. and stock returns in China and India is weak in the short term but gradually becomes stronger in the long term, especially when significant financial events occur. There is no Granger causality in the short term; however, there is unidirectional or bidirectional causality in the medium and long term. These conclusions may provide useful reference for policymakers and investors in Chinese and Indian stock markets to prevent cross-country risk contagion from the U.S.